THE FACTORS OF NORTH SULAWESI TOURISM BUSINESS POTENTIAL IN THE PERSPECTIVE OF FOREIGN LOCAL TOURISM BUSINESS OWNERS - Pakasi, Zenta M. E. M. A (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT This study was conducted to examine the factors of North Sulawesi tourism business potential in the perspective of foreign local business owners. This study was specifically conducted in four regions of North Sulawesi, Manado city, Bitung city, South – east Minahasa, Bunaken island and Siladen island. The method used in this research is descriptive qualitative exploratory. The population in this study consisted of foreign local business owners. The results showed that the diversity that North Sulawesi has makes the foreign business owners running their business in North Sulawesi and also helping the quality of local people in the tourism industry. This study also shows that the government regulation holds the foreign business owners back to freely own their own business. North Sulawesi is a land of magnificent coral reefs protecting, active volcanoes, reminding the islanders and Eco – tourism is the most potential that North Sulawesi has.   Key words: Tourism, Foreign local business owners, potential, Eco – tourism